Ideal Teacher Behaviors: Student Motivation and Self-Efficacy Predict Preferences. (April 2013) - Komarraju, Meera
Differences in students' academic self-efficacy and motivation were examined in predicting preferred teacher traits. Undergraduates (261) completed the Teaching Behavior Checklist, Academic Self-Concept scale, and Academic Motivation scale. Hierarchical regression analyses indicated that academic self-efficacy and extrinsic motivation explained 5–23% of incremental variance in the ideal traits of "caring" and "professional." Students who lacked self-efficacy clearly valued the "caring" trait in an ideal teacher. Extrinsically motivated students strongly endorsed the importance of an ideal teacher being "caring" (encouraging and compassionate) and "professional" (knowledgeable and confident). Implications for instructors include rewarding extrinsically motivated student by recognizing their performance and mentoring students who lack self-efficacy.